Evaluation of the usefulness of a computerbased learning program to support student learning in pharmacology - Brain , S.; Dewhurst , D. G.; Williams , A. D. (Research in Learning Technology)
The use of computers in undergraduate education is now widespread and computer-based learning (CBL) has made a significant impact in teaching, particularly over the last decade. This is likely to increase substantially as some £100 million has been made available to stimulate software development in the UK through various initiatives, such as the EEC COMETT program and the UK Higher Education Funding Councils’ Teaching and Learning Technology Programme (TLTP). DOI: 10.1080/0968776990070205